Cars and distraction: How to address the limits of Driver Monitoring Systems and improve safety benefits using evidence from German young drivers. (August 2021) - Jannusch, Tim; Shannon, Darren; Völler, Michaele; Murphy, Finbarr; Mullins, Martin
Abstract: We are facing an increase in the emergence of distracting activities while driving. This is especially the case for young people who, more than other age groups, employ their cars as a place of personal fulfilment. This study proposes an interdisciplinary safe-by-design (SbD) heuristic to address this emerging risk. It harnesses a German version of the Behaviour of Young Novice Driver Scale (BYNDS) to gather representative information about young people's distracting activities. This information is then used to address to limitations of Driver Monitoring Systems (DMS) and posit safety measures in the context of young driver distraction. Our novel approach reveals three recommendations that should guide the employment of DMS in future generations of cars. We argue that the sole use of DMS Type 1 (i.e. vehicle motion data) is not sufficient to cope with the complex range of distracting activities that occur inside the car. We suggest designers and technologists employ DMS Type 2 (i.e. cameras and acoustic sensors) as this makes it possible to capture rich information about humans, objects and their interaction. In light of concerns about data privacy, policymakers must act to regulate the ethical use of data from the inside of the car and to find the necessary trade-off between data privacy and the unnecessary attrition of young human lives. This research provides a reasonable foundation for this discussion. Highlights: This paper introduces an original interdisciplinary safe-by-design (SbD) heuristic. Evidence about distracting behaviours performed by young drivers is provided. Safety measures in the context of young driver distraction are provided. The potential of monitoring systems to address driver distraction is analysed.